2015
DOI: 10.1021/acs.jpcc.5b10243
|View full text |Cite
|
Sign up to set email alerts
|

Self-Radiolysis of Tritiated Water Stored in Zeolites 4A: Production and Behavior of H2 and O2

Abstract: Radiolysis of confined water and self-radiolysis of tritiated water gives rise to several unanswered questions. To take into account this double specificity, we studied systems of zeolites 4A containing tritiated water at different water loading ratios. Two tritiated water were synthesized at the volumetric activities of 27 TBq.L-1 and 60 TBq.L-1. For each one, five samples were prepared, differentiated by their water loading ratios, expressed in percentage, close to 4, 7, 11, 14 and 19 %. The study of the rad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 35 publications
2
6
0
Order By: Relevance
“…As the surface catalyses the dissociation of dihydrogen and dioxygen molecules, its coating by water prevents both from interacting with the surface. Acres thus shows the necessity for the molecules to be in contact with the adsorbing surface in order to be activated, in good agreement with the observations from experimental works by L. Frances et al 1 concerning the delay-ing effect of water on the decrease of the amounts of O 2 and H 2 molecules in zeolite. L. Morales 10 , who studied the recombination on a plutonium dioxide surface, emphasizes the important role of catalyst that the surface plays in the reaction and minimizes that of the radicals formed during radiolysis.…”
Section: Introductionsupporting
confidence: 90%
See 2 more Smart Citations
“…As the surface catalyses the dissociation of dihydrogen and dioxygen molecules, its coating by water prevents both from interacting with the surface. Acres thus shows the necessity for the molecules to be in contact with the adsorbing surface in order to be activated, in good agreement with the observations from experimental works by L. Frances et al 1 concerning the delay-ing effect of water on the decrease of the amounts of O 2 and H 2 molecules in zeolite. L. Morales 10 , who studied the recombination on a plutonium dioxide surface, emphasizes the important role of catalyst that the surface plays in the reaction and minimizes that of the radicals formed during radiolysis.…”
Section: Introductionsupporting
confidence: 90%
“…On the one hand because of the competition between the two molecules (O 2 and H 2 O) for the occupation of the cationic sites, on the other hand because of the congestion created by the water molecules forming rings between them via hydrogen bonds and Na + cations. One of the direct consequences of this phenomenon was observed experimentally by L Frances et al 1 on the consumption of the gaseous phase composed, among other elements, of O 2 that has been released following the radiolysis of water in Na-A zeolite (figure 13). The delay between each decrease in the O 2 component is closely related to the amount of water present in the structure, i. e. the water loading rate that is indicated in mass % in the results.…”
Section: O 2 Adsorptionmentioning
confidence: 87%
See 1 more Smart Citation
“…Previous studies dealing with the radiolysis of zeolites with adsorbed water agree to the point that irradiation of the solid matrices of the zeolites induces decomposition of water in the pores resulting in H 2 production. The energy/charge transfer from the zeolites was confirmed by pulse radiolysis studies of excess electrons in hydrated zeolites. The pulse radiolysis studies concluded that generation of excess electrons hydrated in the zeolite pores occurred at yields greater than hydrated electron (e – aq ) during the radiolysis of bulk water. The high yields of e – aq would qualitatively explain the H 2 production by the irradiation of hydrated zeolites because e – aq is a main precursor of H 2 in water radiolysis. , However, understanding radiation-induced reactions in zeolites is not sufficient to estimate the yield of H 2 because the reaction scheme of H 2 production is not well-defined .…”
Section: Introductionmentioning
confidence: 74%
“…The hydrogen production by water radiolysis in zeolite was also studied, 30,31 and zeolites type A4 (Na) were subject to numerous investigations as they were used to store tritiated water, or for the decontamination of Three Mile Island water. With zeolites, the importance of energy transfer from the matrix to the porous water was clearly observed.…”
Section: Introductionmentioning
confidence: 99%